MODERATING ROLE OF FINANCIAL PERFORMANCE ON BOARD ATTRIBUTES AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE OF LISTED NON-FINANCIAL FIRMS IN NIGERIA - Balarabe, Bishir; Idris, Adamu Adamu; Muhammad, Musa Musa (Kashere Journal of Management Sciences, 2025)
This study aims to explore the direct and moderating impact of firm financial performance on the relationship between corporate social responsibility disclosure, board meetings, and diversity in listed non-financial corporations in Nigeria. The population of the study consists of 161 listed non-financial firms on the floor of the Nigerian Exchange Group. The study uses 62 companies from the total companies using purposive sampling. The study covers a ten-year period from 2014–2023. To assess the data, OLS regression model was employed. According to the study's findings, board diversity was found to be statistically significant in the direct model. Moreover, profitability was found to moderates the relationship between board meetings and corporate social responsibility disclosure. Thus, indicating, in a profitable firm, higher board meetings will result in greater corporate social responsibility disclosure.